Development of Preventive Dental Guidelines in the Primary Healthcare Setting in Egypt: A Delphi Method - mehriz, basant (AUC Knowledge Fountain, 2025)
This study addresses the critical need for standardized preventive dental care guidelines within Egypt's primary healthcare system amid the rising burden of oral diseases. Through a systematic two-phase methodology combining a comprehensive literature review and a Delphi consensus-building process engaging 35 dental professionals, the research established priorities for contextually appropriate preventive measures. The consensus framework revealed strong support for clinical interventions (mean of 83% agreement), particularly fluoride-based prevention; community initiatives (mean of 83%), especially school-based programs; policy measures (mean of 77%) such as workforce and educational development, though with variable support for taxation and social determinants approaches. Statistical analysis demonstrated progressive convergence of expert opinions across rounds, yielding a hierarchical implementation framework categorized by priority level. The resulting evidence-informed guidelines provide Egyptian policymakers with a structured approach to integrate preventive dental services within primary healthcare, potentially enhancing oral health outcomes and healthcare equity nationwide. This research addresses a significant gap in Egypt's oral healthcare infrastructure by providing a blueprint for sustainable, context-appropriate preventive dental strategies.